Analisis Penerapan Aplikasi Si Apik Untuk Memenuhi Kebutuhan Informasi Akuntansi Pada UMKM (Studi Kasus pada UMKM Corndog SCJ Jepara) - Rohman, Fatchur; Zaenal Anwar, David (Jurnal Rekognisi Akuntansi, 2023)
This study aims to implement a new accounting information system using an Android-based accounting application to meet the needs of small, micro and medium enterprises. The results of the research can be used to assist the process of recording and reporting finances, so that companies can find out the profit or loss that the company generates. This type of research is applied research. Researchers used a qualitative approach to the method of descriptive analysis techniques. This study uses data collection techniques by interviewing, observation and documentation. Based on the results of the research that has been done, it can be concluded that using the Si Apik application can help MSME actors meet the needs of accounting information systems in companies. The Si Apik application assists companies in keeping accounting records and carrying out good financial reporting and in accordance with applicable regulations.